Electromagnetic concepts and applications - DuBroff, Richard E. (Prentice Hall, 1996)
This text provides an in-depth and applications oriented approach to introductory electromagnetics, but at the same time offers student-friendly features that keep students interested and that develop confidence and competence by clearly and continually drawing and building on material that is usually addressed in prerequisite physics courses.